Constraints to agricultural finance in underdeveloped and developing countries: a systematic literature review - Farman Ullah Khan; Muhammad Nouman; Lucia Negrut; Junaid Abban; Laura Mariana Cismas; Muhammad Fahad Siddiqi (International Journal of Agricultural Sustainability)
Agricultural finance plays a pivotal role in facilitating the modernization and commercialization of farming practices and bolstering global food security. However, the provision of sustainable financial services in remote regions poses a significant challenge within the developing and underdeveloped countries. Consequently, farmers often grapple with inadequate access to formal credit sources and essential productive assets due to diverse constraints. Although, several studies have investigated constraints to agriculture finance; the literature is divergent and a holistic framework of constraints to agriculture finance is missing. Therefore, this research explores the constraints to agriculture finance in 31 developing and underdeveloped countries using systematic review approach, and synthesizes a holistic framework of the constraints using Qualitative Evidence Synthesis (QES) method that can be used as dependable framework for conceptualization and policy formation. Moreover, it describes the interplay and mutual reinforcement between the challenges faced by different stakeholders to elaborate how they influence each other in complex ways. Additionally, this study suggests a collective and multi-faceted approach for overcoming barriers to agricultural financing, and highlights the limitations and unintended consequences of agricultural credit and its implications for agricultural sustainability.